Prototype of Gas Leaking Monitoring Device In Gas Distribution Pipe of PT. Prima Gasifikasi Indonesia in Tanjung Batu - Eko Prayetno; Deny Nusyirwan; Ryan Ramadhan Putra; Randika Saputra; Bayu Anggara (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2020)
This study aims to help PT. Prima Gasifikasi Indonesia makes a device that detects leaks in gas distribution pipes based on microcontroller technology. This gas detector is connected to several virtual devices that make this tool work well, namely the MQ-2 sensor working as a gas detector, NodeMCU to control the device's controls. As a notification sender to Android, the LED indicates the tool is active, and the buzzer is the provider. Information with a voice indicator. This detector can detect gas to a 'distance 'of less